1987
DOI: 10.1016/0014-5793(87)80430-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction and activation of tissue transglutaminase during programmed cell death

Abstract: During the involution of lead nitrate-induced hyperplasia in rat liver a significant increase of transglutaminase activity, enzyme concentration, transglutaminase messenger RNA and protein-bound e-@-glutamyl)lysine (product of transglutaminase action) coincided with programmed death (apoptosis) of hepatocytes. Immunohistochemical examination showed the appearance of transglutaminase in apoptotic hepatocytes. An increased transglutaminase level was also detected during glucocorticoid-induced apoptosis of rat th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
192
1
8

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(204 citation statements)
references
References 25 publications
3
192
1
8
Order By: Relevance
“…Tissue transglutaminase (TGase) has been shown to be upregulated in cells undergoing apoptosis, raising the possibility that it is a pro-apoptotic protein (7)(8)(9)(10)(13)(14)(15)(16). However, recent studies examining the role of TGase in RA-mediated differentiation have shown that it provides protection against apoptosis (12) and may be important for cellular differentiation (19,33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue transglutaminase (TGase) has been shown to be upregulated in cells undergoing apoptosis, raising the possibility that it is a pro-apoptotic protein (7)(8)(9)(10)(13)(14)(15)(16). However, recent studies examining the role of TGase in RA-mediated differentiation have shown that it provides protection against apoptosis (12) and may be important for cellular differentiation (19,33).…”
Section: Resultsmentioning
confidence: 99%
“…The transamidation reaction of TGase has been well studied and consists of the Ca 2ϩ -dependent formation of covalent bonds between the ␥-carboxamide groups of peptide-bound glutamine residues and the primary amino groups of a wide variety of proteins (1,2). Transamidation has been implicated in a number of biological processes such as axonal regeneration, cellular differentiation, and apoptosis (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Many of the early studies of TGase have identified it as being present in cells and tissues undergoing apoptosis (7-10, 13, 14) and implicated the transamidation activity of TGase as a potentiator of programmed cell death (15,16).…”
mentioning
confidence: 99%
“…TGase 2 is a calcium-dependent enzyme that catalyzes the formation of covalent bonds between free amine groups in one protein and protein-bound glutamines of another, creating highly cross-linked protein complexes (4). TGase 2 is ubiquitously expressed and has multiple normal physiologic functions through the targeting of specific substrates, such as blood clotting (5), wound healing (6), cell adhesion (7), apoptosis (8), and barrier formation (9). TGase 2 has also been associated with certain pathologic conditions [i.e., inflammatory diseases, such as encephalomyelitis (10), inflammatory myopathies (11), and celiac disease (12), as well as various types of cancer (1)(2)(3)(13)(14)(15)(16)(17)].…”
Section: Introductionmentioning
confidence: 99%
“…During the years, it became clear that the enzyme overexpression occurred during phases of embryonic cell regression in organogenesis (e.g. in the foot interdigital membranes), that this same process could appear during regression after experimental induction of tissue hypertrophy (as proved by Laszlo Fesus in the liver of animals treated in vivo with lead salts) (Fesus et al 1987) and that in all these instances the death of the cells took place by apoptosis (Fesus et al 1991(Fesus et al , 1996. This link between transglutaminase 2 and programmed cell death has deeply influenced all successive transglutaminase research, including manipulation of transglutaminase expression for therapeutic goals, as occurred in the treatment of certain forms of leukemia (typically the promyelocytic leukemia, in which two cycles of treatment are effective in healing definitively over 85% of the patients) (Benedetti et al 1996;Ozpolat et al 2001;Asou 2007).…”
Section: The Years Of the Genementioning
confidence: 99%